Penerapan Asas Pacta Sunt Servanda dalam Jual Beli Online dengan Sistem Cash on Delivery (COD) - Sevina Rezika Hasibuan; Lilawati Ginting (Talenta Publisher, 2024)
This study examines the implementation of the Pacta Sunt Servanda principle in online buying and selling, specifically focusing on transactions using the Cash on Delivery (COD) system. The study emphasizes the importance of adhering to this principle to ensure that neither party is harmed in the transaction. However, it highlights that many sellers face disadvantages when buyers unilaterally terminate the agreement by refusing payment in COD transactions. The principle of pacta sunt servanda, which is binding and requires parties to comply with the agreed-upon terms, serves as the basis for the sale and purchase agreement and aims to minimize losses for buyers. The study concludes that Indonesian positive law regulates online transactions using the COD system and outlines legal consequences for buyers who do not follow the procedures, such as account blocking and reimbursement of costs and losses. Additionally, sellers are encouraged to seek legal protection and demand fulfillment of the buyer's obligations through legal action such as compensation claims. Penelitian ini mengkaji implementasi asas Pacta Sunt Servanda dalam jual beli online, secara khusus berfokus pada transaksi yang menggunakan sistem Cash on Delivery (COD). Studi ini menekankan pentingnya mematuhi prinsip ini untuk memastikan bahwa tidak ada pihak yang dirugikan dalam transaksi. Namun, studi ini menyoroti bahwa banyak penjual yang dirugikan ketika pembeli secara sepihak mengakhiri perjanjian dengan menolak pembayaran dalam transaksi COD. Asas pacta sunt servanda, yang mengikat dan mengharuskan para pihak untuk mematuhi persyaratan yang telah disepakati, menjadi dasar perjanjian jual beli dan bertujuan untuk meminimalkan kerugian bagi pembeli. Studi ini menyimpulkan bahwa hukum positif Indonesia mengatur transaksi online dengan sistem COD dan menguraikan konsekuensi hukum bagi pembeli yang tidak mengikuti prosedur, seperti pemblokiran akun dan penggantian biaya dan kerugian. Selain itu, penjual didorong untuk mencari perlindungan hukum dan menuntut pemenuhan kewajiban pembeli melalui upaya hukum seperti tuntutan ganti rugi.